From beginning to mature: investigating the development of teacher community through Lesson Study - Ni Shuilleabhain, Aoibhinn; Owens, Emma; Seery, Aidan; Hyland, Diarmaid (Frontiers in Education, 2024)
This research investigates the potential of Lesson Study to develop teachers’ professional community. Situated in two case study schools, Doone and Crannog (both pseudonyms), where mathematics teachers participated in multiple, successive cycles of Lesson Study over the course of one academic year, the research details the development of teacher community through teachers’ conversations and reflections. Data was generated through audio recordings of teachers’ Lesson Study meetings and individual interviews with participating teachers. Analysis is based on a framework of professional teacher community which describes discrete phases of development from beginning to mature. Findings from the research suggest that groups of teachers may begin their Lesson Study work at different stages of evolution of teacher community and that Lesson Study has the potential to strength and develop such community over successive cycles. The research demonstrates that teachers’ participation in Lesson Study can provide them with opportunities to recognize and express communal responsibility for individual growth of colleagues, a key feature in the formation of teacher community. The research also highlights the importance of navigating fault lines or differences in ideas and opinions during the Lesson Study work. Findings may offer guidance to facilitators of Lesson Study on elements of teachers’ collaborative work which may benefit from additional focus, such as productively engaging with conflict within a group. This research contributes to the literature on Lesson Study in outlining how this model of professional development may provide a powerful structure within which teacher community can be developed.